Community Based Biofiltration for Hard Water Treatment in Rural Indonesia: A Public Health Oriented Approach - Annisa Melania; Syamsuar Manyullei; Hasanuddin Ishak; Hasnawati Amqam; Healthy Hidayanty; Syamsiar S. Russeng (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Clean water accessibility remains a persistent challenge in rural Indonesia, especially in regions with naturally hard groundwater. This study evaluated the effectiveness of a novel dual-media biofiltration system that integrates activated carbon from Schleichera oleosa (Kesambi wood) and rice husk ash two locally abundant materials to address hard water contamination in Lanca Village, South Sulawesi. This synergistic combination represents an innovative, low-cost approach with both environmental and public health benefits in rural water treatment. Methods: Utilizing a quasi-experimental design, three water samples (n = 3) were tested for levels of CaCO?, Ca²?, Mg²?, and Fe before and after filtration. Results: The filtration system achieved substantial reductions: total hardness (CaCO?) decreased by 55.78%, calcium by 65.99%, magnesium by 40.40%, and iron by 100%. Although these changes did not reach statistical significance (p > 0.05) due to the small sample size, the experimental filter outperformed a palm fiber-based control filter across all parameters. Conclusion: The study highlights the biofilter’s role not just as a technical solution, but as a promotive health technology leveraging local materials to meet national water standards while enhancing community resilience. The findings underscore its practical applicability in achieving SDG 6.1 and offer a scalable, sustainable solution for decentralized rural water treatment.